EFFECT OF 5 ANIMAL MANURES (PIG, POULTRY, RABBIT, CATTLE, AND SHEEP) ON NUTRITIONAL QUALITY OF EARTHWORM MEAL (EISENIAFETIDA) IN VERMICOMPOST. - VODOUNNOU, D.S.J.V.; KPOGUE, D.N.S.; DJISSOU, Arnauld Sedjro Martin; MENSAH, GUY APOLLINAIRE; FIOGBE, EMILE DIDIER (My University, 2016)
Earthworms were cultured with five animal manures firstly, harvested and dried. The aim of the study was to evaluate the effect of pig, poultry, rabbit, cattle, and sheep manures on the nutritional quality of earthworm meal. The Growth parameters of earthworm production and biochemical parameters of earthworm meal were determined. At the end of the study, the growth parameters of earthworm production and the biochemical parameters of earthworm meal varied with the different used substrates (P<0.05). The produce (worm g/ Kg substrate) were: 41.33 ± 3.27 for cattle manure >36.11 ± 2.70 obtained in pig manure >22.11 ± 4.73 recorded in rabbit manure >10.55 ± 2.28 observed in poultry manure >2.66 ± 1.61 for sheep manure. The highest protein rate (51.38±0.05%) in earthworm meal was obtained in pig manure and the lowest (42.45±0.08%) sheep manure. The earthworm production and the biochemical quality of earthworm meal are greatly affected by the earthworm feeding substrates.
Keywords: Effect; animal manures; earthworm meal; nutritional quality